AN EXPLORATORY STUDY OF ERRORS IN ORAL PERFORMANCE OF ENGLISH LANGUAGE LEARNERS - Mehdi, Yusuf; Kumar, Shravan (International Journal of Psychosocial Rehabilitation, 2020)
While learning a new language, the learners make a lot of errors related to syntax and semantics. The present study aims at analysing the errors made by learners of English language. This study analysed students ’errors and the causes during speaking performance by 7 students learning English at Integral University, Lucknow. The audio recordings of the students, introducing themselves after 2 weeks of language classes, were used to find errors. The data was analysed by identifying the errors, and by grouping and tabulating those into category codes. The four category method of speaking errors was used to analyse and interpret the data. The four categories of speaking errors used were incorrect omissions, redundancy, misused words, and confused forms. The study also analysed various causes of errors that influenced the learners in speaking namely interlingual transfer, intra-lingual transfer, learning context, and communication strategies.